Obstacles to the collection and distribution of state resources in the Prophetic Age - bin Omairah, Bader Hayef (Journal of Humanities & Social Sciences, 2017)
This study deals with the obstacles faced by the emerging Islamic state in one aspect of its administration, especially the financial aspect, where the collection and distribution of state resources, controversy over the distribution of spoils, refrain from performing Zakat, Counter propaganda against the spenders, The behavior of some workers. The approach of the messenger of Allah has played a prominent role in addressing these obstacles, he succeeded in maintaining the national’s unity and emerged coherently. Perhaps in this research we revealed the most important of these obstacles and show the face of the problem in it, and to show the prophetic approach in the which he addressed these obstacles.